Fyn Signaling in Ischemia-Reperfusion Injury: Potential and Therapeutic Implications - Fang Du; Tao Tang; Qingzhu Li; Jiaxin Liu (Mediators of Inflammation)
Ischemic stroke caused by arterial occlusion is the most common type of stroke and is one of the leading causes of disability and death, with the incidence increasing each year. Fyn is a nonreceptor tyrosine kinase belonging to the Src family of kinases (SFKs), which is related to many normal and pathological processes of the nervous system, including neurodevelopment and disease progression. In recent years, more and more evidence suggests that Fyn may be closely related to cerebral ischemia-reperfusion, including energy metabolism disorders, excitatory neurotoxicity, intracellular calcium homeostasis, free radical production, and the activation of apoptotic genes. This paper reviews the role of Fyn in the pathological process of cerebral ischemia-reperfusion, including neuroexcitotoxicity and neuroinflammation, to explore how Fyn affects specific signal cascades and leads to cerebral ischemia-reperfusion injury. In addition, Fyn also promotes the production of superoxide and endogenous NO, so as to quickly react to produce peroxynitrite, which may also mediate cerebral ischemia-reperfusion injury, which is discussed in this paper. Finally, we revealed the treatment methods related to Fyn inhibitors and discussed its potential as a clinical treatment for ischemic stroke.